Supplement of manuscript 521330 - Elferink, Stephanie; Wohlrab, Sylke; Neuhaus, Stefan; Cembella, Allan; Harms, Lars; John, Uwe (Zenodo, 2020)
This folder contains analysis data from the study submitted as manuscript (Manuscript ID 521330): TITLE: Comparative metabarcoding and metatranscriptomic analysis of microeukaryotes within coastal surface waters of West Greenland and Northwest Iceland AUTHORS: Stephanie Elferink, Stephanie.westphal@awi.de, Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research Sylke Wohlrab, Sylke.wohlrab@awi.de, Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research, and Helmholtz Institute for Functional Marine Biodiversity Stefan Neuhaus, Stephan.neuhaus@awi.de, Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research Allan Cembella, Allan.Cembella@awi.de, Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research Lars Harms, Lars.Harms@awi.de, Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research, and Helmholtz Institute for Functional Marine Biodiversity Uwe John, Uwe.John@awi.de, Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research, and Helmholtz Institute for Functional Marine Biodiversity JOURNAL: Frontiers in Marine Science, section Marine Molecular Biology and Ecology MS-ID: 521330 HOWTO: Sequences identified as Alveloates or Stramenopiles (description in manuscript) had been were classified more accurately by PhyloAssigner version 6.166 (https://github.com/jungbluth/phyloassigner, Vergin et al., 2013, DOI:10.1038/ismej.2013.32) with a phylogenetic placement onto reference trees based on 18S/28S concatenated alignments, according to Elferink et al. 2017 (DOI: 10.1016/j.dsr.2016.11.002). CONTENT: reference databases: - Alveolata_SSU-LSU-concat_310715_636.phyloassignerdb - Stramenopiles_SSU_LSU_concat_030815_1777.phyloassignerdb query sequence files: - Alveolata_seqtab_SIGN_dada2.fasta - Alveolata_seqtab_SIGN_dada2.fasta created out put folder including the taxonomic annotation: - Alveolata_seqtab_SIGN_dada2.place.out - Stramenopiles_seqtab_SIGN_dada2.place.out text file containing the used commands: - commands